2018
DOI: 10.4149/bll_2018_116
|View full text |Cite
|
Sign up to set email alerts
|

Association between interleukin 4 (IL-4) VNTR, gene polymorphism, and breast cancer susceptibility in Iranian population: experimental and web base analysis

Abstract: BACKGROUND: Breast cancer (BC) is one of the most common types of cancer and the second leading cause of cancer death among women. Epidemiological studies showed that BC is linked to genetic and environmental factors, and inheritance plays a key role in the pathobiology of this disease. Interleukin 4 (IL-4) is a key differentiation cytokine and is produced by Th2 and activates Th2 development. Hence the current study aimed to assess the possible association between interleukin 4 (IL-4) VNTR polymorphism, and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Although cachexia is generally observed in pancreatic, gastric, colorectal, lung, and head and neck cancer, recent studies have provided a compelling evidence that there is a relationship between advance metastatic breast cancer and cachexia due to a decrease in muscle mass and excessive weight loss (53)(54)(55). Recent studies have also demonstrated that a high level of IL-6 is associated with cachexia, angiogenesis, atrophy, increased catabolism of muscle protein and resistance to treatment in advance breast cancer (2,35,56).…”
Section: Discussionmentioning
confidence: 99%
“…Although cachexia is generally observed in pancreatic, gastric, colorectal, lung, and head and neck cancer, recent studies have provided a compelling evidence that there is a relationship between advance metastatic breast cancer and cachexia due to a decrease in muscle mass and excessive weight loss (53)(54)(55). Recent studies have also demonstrated that a high level of IL-6 is associated with cachexia, angiogenesis, atrophy, increased catabolism of muscle protein and resistance to treatment in advance breast cancer (2,35,56).…”
Section: Discussionmentioning
confidence: 99%
“…2R/2R carrier genotypes (3R/2R and 2R/2R) were reported to be associated with late stage bladder cancer in northern Indian population (28) and 2R/2R genotype refl ected a signifi cant association for bladder cancer and tumor invasiveness in a Taiwanese population (29). Concertedly with previous studies, 3R/3R genotype of IL-4 VNTR was proven as a protective factor against breast cancer susceptibility in an Iranian population (30) while the effect of IL-4 VNTR variants was not observed in Jordanian breast cancer patients (31). In adult acute myeloid leukemia patients, the frequency of 3R alleles was higher than in controls and 3R/3R genotype was reported to be signifi cantly associated with poor therapeutic response, higher susceptibility to disease recurrence and shorter overall survival and disease-free survival (32).…”
Section: U N C O R R E C T E Dmentioning
confidence: 65%
“…In a recent study, Ibrahimi et al suggested that RP2\RP2 genotypes might be a potent protective factor against BC 39. In addition, Jia et al40 examined in a comprehensive meta-analysis the correlation between different types of genetic variants within the IL-4 gene, including the VNTR, and cancer risk.…”
Section: Discussionmentioning
confidence: 99%